MILDER CRIMINAL STATUTE AND LIMITS OF ITS APPLICATION IN THE JURISPRUDENCE OF LITHUANIAN COURTS - Švedas, Gintaras (Teisė, 2016)
Article deals with the concept and content of the milder criminal statute, kinds of milder criminal statute and limits of its application in the jurisprudence of Lithuanian courts.The Criminal Code of The Republic of Lithuania regulates in sufficient detail the conception of milder (stricter) criminal law and the limits of its application. Para 2 of Article 3 of the Criminal Code of Lithuania provides that “a criminal law nullifying the criminality of an act, commuting a penalty or in otherwise mitigating legal circumstances for the person who committed the criminal act shall have a retroactive effect, i.e., it shall apply to the persons who committed the criminal act prior to the coming into force of such a law, also to the persons serving a sentence and those with previous convictions”.Criminal statute nullifying the criminality of an act is a law which no longer provides for former corpus delicti (full decriminalisation) or narrows its composition by providing new or eliminating former features of corpus delicti (partial decriminalisation), hence certain actus reus become non-criminal.Criminal statute commuting a penalty, may be recognized as a law which reduces the minimum, maximum or both terms of the imprisonment provided in the sanction of the Article of CC, or reduces the minimum, maximum or both terms of the kind of penalty provided in the Article of General Part of CC, or provides for new one or few milder kinds of penalties in the sanction of the Article of CC, etc.Criminal statute in otherwise mitigating legal circumstances for the person who committed the criminal act is a law which removes an act from the list of serious crimes, extends the possibility of releasing the person who committed the criminal act from criminal liability or penalty or suspend the execution of penalty conduct, establishes a more favourable kind and regime of a correctional institution, provides more favourable conditions for paying fines, shortens the prescription period, duration of conviction, etc.Analysis of jurisprudence of The Supreme Court of Lithuania shows that courts usually make mistakes in the process of establishing the limits of retroactive application of criminal law (to people serving imprisonment sentences), which is commuting a penalty or is in otherwise mitigating circumstances for the person who committed the criminal act.